(untitled) (Agro Productividad, 2021)
Objective: To characterize family production units (FPUs) to identify critical points for their activities and propose intervention strategies for them. Design/methodology/approach: The research took place at Yaxcabá municipality, state of Yucatán, Mexico. It is descriptive and its information obtained through 1) a questionnaire in a mobile application compatible with the Android operating system, structured by modules: producer data, FPU characteristics, crops, infrastructure, machinery, equipment, and marketing. The sample size was randomized with replacement, under the maximum variance condition, 2) assessment visits to the farmer’s plots and 3) participatory community diagnosis workshops. Results: The traditional milpa system was oriented to the cultivation of corn, beans and squash of creole origin, for consumption by the FPUs with minimum technologies usage. Through apiculture, producers obtain an economic resource to finance other activities, including those of the milpa. It is, therefore, necessary to strengthen their productive capacities of this activity with a chain approach, for the diversification of their products and derivatives of their hives that allow their income to increase. Limitations on study/implications: The proposals and intervention strategies may only be applied to the production system in the evaluated area. Findings/conclusions: The strategies for the traditional milpa production should be oriented to food security, biodiversity preservation and the nutritional health of their related population. Apuculture strategies should aim to include producers in the value chain.